KOMUNIKASI MATEMATIKA TERTULIS SISWA BERKEMAMPUAN MATEMATIKA RENDAH DALAM PEMECAHAN MASALAH SOAL HOTS BERDASARKAN JENIS KELAMIN - Arezqi Tunggal Asmana (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2020)
This research aims to describe the written mathematics communication of students with low mathematical ability in solving HOTS problems based on gender. This research is a qualitative research because the main data about the accuracy, completeness, and fluency of written mathematics communication in the form of written words. The research subjects were 2 students with low mathematical ability in class XI MIPA MAN 1 Lamongan consisting of one male and female student. The results showed that there were slight differences in the written mathematics communication of male and female students in the fluency of the information conveyed.